Trends, challenges and innovations in Indian banking sector - Rengasamy, Dhanuskodi (2015)
Banks play a very important role in the economic development of every nation. It plays a vital role to attain stable prices, high level of employment, sound economic growth etc. As stated by the (ACARAVCI and ÇALIM 2013) that the banks plays a crucial role in the operation of most economics. India is the largest economy in the world having more than 1 billion population. Indian service sector contributes major role (Half) in their GDP and the banking sector is the leading service sector in Indian economy. The objective of research is to examine the trends, challenges and innovations in Indian Banking Sector. The trends have been assessed through linear trend by consider bank balance sheet components, resource mobilisation, market expansion and profitability. The challenges of Indian banks are identified through literature and secondary data are capital norms, risk management, information and technology, competition, customer expectation etc. The Indian banking sector always contributes remarkable role in innovations, the technological innovation in the banking operation is remarkable. The study mainly considers the technological innovations in the Indian banking sector.